MEMBACA KONSEP INSAN KAMIL IBN ‘ARABI MELALUI PSIKOLOGI TRANSPERSONALISME - Nawtika, Titian Ayu; Yuslih, Muhammad (Mazalat: Jurnal Pemikiran Islam, 2023)
The concept of Insan Kamil Ibn ' Arabi in the perspective of transpersonalism with the dimension of faith based on the essence of monotheism in the process of perfecting faith through an intuitive approach, Man is a reflection of the analogy of God the radiances of God and in man all the qualities collected in Man are bodily and mental, man who is aware of himself then he will know his Lord, when man loses his afterlife attributes and attaches importance to the mortal world then he will become a human Hayawan. This study aims to determine the concept of Insal Kamil Ibn ‘Arabi in the perspective of transpersonal psychology. This study is a library research whose data is obtained from the results of reading and collecting books related to this study. adpaun data sources in this study there are two primary data and secondary data. Primary Data relate to books written directly by Ibn ‘Arabi. Then the secondary data is a variety of books, articles, the internet that can support this research. Then the data were analyzed using descriptive, historical and holistic methods. Based on research conducted, it can be seen that, in actualizing the basic potential of human spiritualtas according to Ibn ‘Arabi can be viewed from the theory of transpersonalism. As has been theorized, as follows. First, the knowledge of the soul. Second, the highest levels of achievement. Third, the highest stage of awareness of unity, and fourth, the perfect servant. Where each part is reviewed by the theory. Therefore, man in understanding his basic potential as a human being is not only related to matter as the physical form of man, but far from it, man also through a metaphysical approach to achieve perfection.